2020
DOI: 10.1002/hep4.1635
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Outcomes Following Transesophageal Echocardiography in Patients With Cirrhosis and Esophageal Varices

Abstract: Despite scant evidence, current guidelines indicate that esophageal varices are a relative contraindication to transesophageal echocardiography (TEE). The aim of this study is to compare the risk of gastrointestinal bleeding following TEE among cirrhotic patients with and without endoscopically-documented esophageal varices. This is a retrospective analysis of patients with cirrhosis who underwent upper endoscopy within 4 years of TEE at five institutions between January 2000 and March 2020. Primary outcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…We identified 21 studies comprising 4050 patients evaluating outcomes of TEE in patients with cirrhosis 19‐40 ; TEE was performed intraoperatively prior to liver transplantation in 9 studies ( n = 3015) and for other indications (e.g., cardiopulmonary evaluation or rule out infective endocarditis) in 12 studies ( n = 1035). The clinical characteristics of included studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 21 studies comprising 4050 patients evaluating outcomes of TEE in patients with cirrhosis 19‐40 ; TEE was performed intraoperatively prior to liver transplantation in 9 studies ( n = 3015) and for other indications (e.g., cardiopulmonary evaluation or rule out infective endocarditis) in 12 studies ( n = 1035). The clinical characteristics of included studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies failed to adequately adjust for confounders that could affect the risk of bleeding. While most studies provided descriptive data on cirrhosis severity (e.g., MELD score, Child Turcotte Pugh class) and parameters of coagulopathy (e.g., platelet count, INR, fibrinogen), only one study performed multivariable analyses of risk of bleeding adjusting for these factors 39 . While some studies reported prior endoscopic findings, prior endoscopic intervention, and/or history of variceal bleeding, only three studies reported the proportion of patients taking nonselective beta‐blockers 22,37,39 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our retrospective, multicenter study of patients with cirrhosis who underwent TEE in the Mass General Brigham Health system, we identified no instance of overt gastrointestinal hemorrhage, regardless of whether varices were present. 2 We are concerned that the analysis by Hui and Leung likely overestimates the incidence of bleeding with diagnostic TEE by including non-operative therapeutic TEE cases as well as a large study that relied solely on International Classification of Diseases codes for outcome measures. 3 Moreover, in many instances, post-procedure blood loss appears to be principally related to underlying comorbid disease (e.g., cirrhosis) rather than the actual presence of varices, as evidenced by the authors' (and our own) finding that patients with cirrhosis and varices have no higher risk of bleeding than patients with cirrhosis and no varices.…”
mentioning
confidence: 99%